FACTORS INFLUENCING DELAY IN SEEKING MEDICAL CARE AMONG CANCER BREAST PATIENTS IN BALUCHISTAN: EXPLORE REASONS BEHIND DELAYED PRESENTATION AND HOW PATIENT EDUCATION OR COMMUNITY PROGRAMS MIGHT IMPROVE EARLY ACCESS TO CARE - KHAN, A; ARBAB, R; MAHMOOD, M; KHAN, MI; ARSHAD, A; ANWAR, R (Biological and Clinical Sciences Research Journal, 2024)
Breast cancer is one of the most prevalent and deadly forms of cancer affecting women globally, and Pakistan is no exception. Objective: The main objective of the study is to find the factors influencing delay in seeking medical care among cancer breast patients and explore reasons behind delayed presentation and how patient education or community programs might improve early access to care. Methodology: This cross-sectional study was conducted at Bolan Medical College Quetta Pakistan during January 2024 till June 2024. Data were collected from 125 breast cancer patients who had been diagnosed with the disease at various stages. Results: Data were collected from 125 patients, majority of participants (70%) were aged between 40-60 years, with a mean age of 50.01 ± 7.61 years. Most were married (60%) and had attained high school education (65%). Employment status indicated that 55% of participants were unemployed, while 35% were engaged in low-paying jobs. Regarding healthcare access, 75% of urban participants had timely access to healthcare facilities, compared to only 40% of rural participants, highlighting disparities in healthcare availability. The highest delays were observed in unemployed participants (65%) and those in low-paying jobs (60%), reflecting the impact of economic constraints. Married participants (60%) also reported substantial delays, potentially linked to family dynamics and caregiving responsibilities. Conclusion: It is concluded that delayed presentation of breast cancer in Pakistan is primarily influenced by socio-cultural stigma, financial constraints, limited healthcare access, and psychological barriers.